KAMPANYE SOCIAL ENGINEERING BANK CENTRAL ASIA LEWAT VIDEO ‘DON’T KNOW, KASI NO’ DI KANAL SOLUSI BCA YOUTUBE BAGI NASABAH - Ade Maulidin, Mochamad (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2024)
This research uses a qualitative descriptive method by observing a video entitled Don't Know, Kasi No on the BCA Solutions YouTube Channel and interviews with 20 BCA customers. From this research, it is known that some people, including customers, think that the social media campaign entitled Don't Know, Kasi No carried out by BCA is both understandable and entertaining. The steps are supported by easy-to-digest material presented by legendary advertising stars in Indonesia. However, from research conducted by researchers, it was found that a small number of BCA customers did not understand the message that the talent chosen by the bank wanted to convey. The duration of this video was also mentioned as being long by some customers, even though it was broadcast on YouTube.